Religion and pseudo-religion: an elusive boundary - Pihlström, Sami (International journal for philosophy of religion, 2007)
This paper examines the possibility of setting a boundary between religion and “pseudo-religion” (or superstition). Philosophers of religion inspired by Ludwig Wittgenstein’s ideas, in particular, insist that religious language-use can be neither legitimated nor criticized from the perspective of non-religious language-games. Thus, for example, the “theodicist” requirement that the existence of evil should be theoretically reconciled with theism can be argued to be pseudo-religious (superstitious). Another example discussed in the paper is the relation between religion and morality. The paper concludes by reflecting on the issue of relativism arising from the Wittgensteinian contention that the religion vs. pseudo-religion division can only be drawn within a religious framework, and on Wittgenstein’s own suggestion that the religious person “uses a picture”.